ANALYSIS OF THE DEVELOPMENT OF THE ARCHIVES MANAGEMENT SYSTEM OF THE SHIP OWNED BY THE CLASS II BITUNG PLP BASE - Fahmi Rahmat Afandi; Evi E. Masengi; Steven V. Tarore (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This study aims to analyze the development of a ship archives management system at the Bitung Class II PLP Base and identify inhibiting factors in its development. Ship archives management plays a strategic role in supporting orderly administration, shipping safety, legal compliance, and accountability in the implementation of state duties in the maritime sector. This study uses a qualitative approach with a focus on the development of a ship archives management system at the Bitung Class II PLP Base. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis was conducted descriptively qualitatively through the stages of data reduction, data presentation, and conclusion drawing. The research study uses a public administration perspective and archives management theory that emphasizes the importance of effectiveness, efficiency, accountability, transparency, and archives management based on the archives life cycle. The results of the study indicate that the development of a ship archives management system at the Bitung Class II PLP Base has not been running optimally. The patterns and mechanisms of archives management still tend to be manual, not standardized, and have not fully implemented the complete archives life cycle. The implemented archiving system is also not fully in accordance with national archival regulations and standards, especially in the implementation of SOPs, archive retention schedules, and the use of electronic archives. Furthermore, limited human resources, infrastructure, and the lack of integrated information technology systems contribute to the low effectiveness of archives management. This study also found that factors inhibiting the development of a ship's archives management system include structural and institutional barriers, human resource and organizational culture barriers, and technical and technological barriers.